Study on Fate of Rabies Patients following Canine Animal Bite or Scratch (Ibrahim Cardiac Medical Journal, 2015)
Background & Objective: Rabies is major public health problem in Bangladesh, although little epidemiological information is available about the disease. The present study is, therefore, intended to assess the extent of animal bite and rabies, and the status of post-exposure prophylaxis in Bangladesh.Materials & Methods: Data were retrospectively collected from clinical records and registers of patients with animal bites and rabies cases attended at IDH between January 2010 to December 2012. All the rabies cases were diagnosed clinically and were analysed using descriptive statistics.Result: Of the 276 patients of rabies patients admitted in the Infectious Disease Hospital, Mohakhali, Dhaka during the period 2009 to 2013, about 39% were 10 or